The Antecedent of Gross Domestic Regional Bruto in Jakarta Province, Indonesia - Utami, Anita Fikti; Wijaya, Tony; Sukidjo, Sukidjo (International Journal of Economics and Financial Issues, 2020)
This study aims to determine how the influence of inflation, unemployment, poverty and investment in regional economic growth in Jakarta province for the period of 2008 - 2019. In this study the model used is Error Correction Model (ECM) by looking at the effect on short and long term inter-macroeconomic variables on economic growth in Jakarta Province. The results of the study show that only unemployment has an influence on the long term and has no effect in the short term, while the variables of inflation, poverty and investment have no influence on economic growth in the short and long term. Keywords: macroeconomic variables, GDRP, ECM, Jakarta JEL Classifications: E22, E24 DOI: https://doi.org/10.32479/ijefi.9028